A adoção de metodologias ativas como prática pedagógica: percepção de docentes do curso de Odontologia - MACEDO, Maíra Assunção (2023)
Teaching practice has been widely discussed and disseminated in recent years. Social changes resulting from the emergence of professions and, above all, the need for adaptations to those that already exist are among the main challenges for Institutions in the field of higher education. The adoption of mechanisms and/or methodological resources that favor individual-centered learning has emerged as a central axis for academic discussions in this century. This study aims to demonstrate the reality of the Bachelor's Degree in Dentistry at a private Higher Education Institution in the interior of the State of Maranhão by using active methodologies as a basis for the training of dental surgeons. The research seeks to analyze the perception of teachers of this course, using active resources in their respective disciplines. It is also considered, as part of a basic principle for its implementation, the National Curricular Guidelines – DCN’s and the Course Pedagogical Project – PPC widely analyzed and discussed in the results of this study. To achieve the objectives, the exploratory method was used with the application of field research that was questioned through a quantitative approach with teachers who teach classes from the first to the fourth semester of the course through a representative and non-probabilistic sample. Collection took place through a semi-structured questionnaire and content analysis, as proposed by Bardin (1977). It is considered, as a result of this study, that teachers have difficulties in understanding the concept and application of active methodologies and it is appropriate for the Institution to promote continued training and improvement in its processes from this teaching-learning perspective.